Moringa oleifera extract mediated the synthesis of Bio-SeNPs with antibacterial activity against Listeria monocytogenes and Corynebacterium diphtheriae. (1st August 2022) - Ao, Bo; Lv, Jing; Yang, Hongmei; He, Fei; Hu, Yuanliang; Hu, Bing; Jiang, Honglin; Huo, Xixiang; Tu, Junming; Xia, Xian
Abstract: Listeria monocytogenes and Corynebacterium diphtheriae are typical bacterial pathogens and pose an increasing threat to food safety and human health due to their growing antibiotic resistance. In this study, biological selenium nanoparticles (Bio-SeNPs) were synthesized by Moringa oleifera extract and selenite. The synthesized Bio-SeNPs were used to treat these two pathogens. They were spherical, and their diameters ranged from 50 to 200 nm according to the TEM result. The element-mapping, FTIR and XPS analyses showed that the Bio-SeNPs consisted of Se(0) and organics produced by M . oleifera . The inhibition zone tests showed that 7 and 0.7 mg/mL of Bio-SeNPs exhibited noticeable inhibition of L . monocytogenes and C . diphtheriae . Furthermore, the growth curve experiments and live/dead cell stain experiments showed that 0.7 mg/mL of Bio-SeNPs could significantly inhibit the growth of these two strains. Morphological observation by SEM showed that L. monocytogenes and C. diphtheriae cells shriveled and broke after treatment with 0.7 mg/mL of Bio-SeNPs. Additionally, the Bio-SeNPs could efficiently clear L. monocytogenes on the raw salmon without cytotoxicity. In particular, the Bio-SeNPs in this study were composed of edible Se(0) and M . oleifera . Accordingly, it exhibited great potential in food and medicine science. Highlights: Bio-SeNPs was synthesized by Moringa oleifera extracts. The Bio-SeNPs were spherical and ranged from 50 to 200 nm. The Bio-SeNPs was consisted of Se(0) and proteins, flavones and polysaccharides . The Bio-SeNPs exhibited excellent antibacterial activity.